Does Compost Improve Young Tree Growth? - Ute Albrecht; Gabriel Pugina; Antonio Castellano-Hinojosa; Sarah Strauss (EDIS, 2022)
This article describes the potential beneficial effects of compost on plant growth.  It summarizes initial results from an ongoing citrus field trial conducted to investigate whether regular compost applications improve soil health, root health, and tree growth and productivity during the early years after planting.